Madoff : the final word - Behar, Richard (Avid Reader Press, 2024)
"Some $68 billion evaporated during Bernie Madoff's epic confidence game. Two people were driven to suicide in the wake of the Ponzi Scheme's exposure. Others went to prison. But there has never been a satisfying accounting for how Bernie got away with so much, for so long. Until now. Richard Behar's relationship with Madoff began in 2011 with a simple email request from the inmate. By the time Madoff died in 2021, he had sent Behar more than 300 emails and dozens of handwritten letters, participated in some fifty phone conversations, and sat for three in-person jailhouse interviews--a level of access provided to no other reporter. Behar also established relationships with hundreds of regulators, prosecutors, FBI agents, investors, Wall Street experts, ex-employees of Madoff's, family members, school classmates, and others. The result is the final word on the criminal behind history's most enduring fraud--and on those who believed him, covered for him, or locked him up. Behar illuminates not only the fraud's origins--decades earlier than Madoff claimed in his confession--but also the complicity of investors, Wall Street insiders, family members, and some of the largest banks in the US and Europe. Shocking, infuriating, riveting (and at times absurdly funny), Madoff shows us how Bernie ensnared thousands of investors. As Behar's dogged reporting over the last fifteen years makes clear, however, there aren't many innocents left standing by the end of this tale. Just about everyone involved is guilty, at a minimum, of humanity's most consistent weakness: greed."--Amazon.